2016
DOI: 10.1021/acs.jafc.5b05577
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin Inhibits Adipogenesis in 3T3-L1 Preadipocytes and Suppresses Obesity in High-Fat Diet-Fed C57BL/6 Mice

Abstract: Obesity is caused by excessive accumulation of body fat and is closely related to complex metabolic diseases. Adipogenesis is a key process that is required in adipocyte hypertrophy in the development of obesity. Curcumin (Cur) has been reported to inhibit adipocyte differentiation, but the inhibitory effects of other curcuminoids present in turmeric, such as demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC), on adipogenesis have not been investigated. Here, we investigated the effects of curcuminoids on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Our previous study also showed that DMC induced the apoptosis of human lung cancer NCI‐H460 cells through the mitochondrial‐dependent pathway . BDMC inhibited adipogenesis in 3T3‐L1 preadipocytes and it had the potential to prevent obesity and induced cell apoptosis in human laryngeal carcinoma cells, activated hepatic stellate cells, and lung cancer NCI‐H460 cells . In human fibrosarcoma cells, DMC or BDMC had higher anti‐metastasis potency than that of CUR via the differentially downregulation of ECM degradation enzymes …”
Section: Introductionmentioning
confidence: 93%
“…Our previous study also showed that DMC induced the apoptosis of human lung cancer NCI‐H460 cells through the mitochondrial‐dependent pathway . BDMC inhibited adipogenesis in 3T3‐L1 preadipocytes and it had the potential to prevent obesity and induced cell apoptosis in human laryngeal carcinoma cells, activated hepatic stellate cells, and lung cancer NCI‐H460 cells . In human fibrosarcoma cells, DMC or BDMC had higher anti‐metastasis potency than that of CUR via the differentially downregulation of ECM degradation enzymes …”
Section: Introductionmentioning
confidence: 93%
“…In addition to curcumin, demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC) curcuminoids are polyphenols present in turmeric. In a study by Lai et al (2016), treatment of 3T3-L1 preadipocytes with BDMC (25 µM) for 30 min resulted in significant repression of lipid accumulation and suppressed adipogenesis by reduced MCE and adipocyte differentiation genes (C/EBPα and PPARγ) protein levels (Table 1) [64]. In addition, BDMC treatment induced cell cycle arrest at the G0/G1 phase and reduced cyclin A, cyclin B, p21 and phosphorylation/activation of MAPKs (phospho-ERK, phospho-p38 and phospho-JNK) levels were reduced [64].…”
Section: Effects Of Curcumin: In Vitro Adipocyte Studiesmentioning
confidence: 98%
“…16 The stability of DMC is higher than that of curcumin, which prevents lipid peroxidation. 17 In recent years, many studies have shown that DMC and curcumin can modulate multiple cell signaling pathways, including apoptosis. [18][19][20] Based on these studies and its structure and function, we hypothesized that DMC may likewise act as a photosensitizer.…”
Section: Introductionmentioning
confidence: 99%